International Olympic Committee consensus statement: harassment and abuse (non-accidental violence) in sport - Mountjoy, M.; Brackenridge, C.; Arrington, M.; Blauwet, C.; Carska-Sheppard, A.; Fasting, K.; Kirby, S.; Leahy, T.; Marks, S.; Martin, K.; Starr, K.; Tiivas, A.; et al. (British Journal of Sports Medicine, 2016)
Despite the well-recognised benefits of sport, there are also negative influences on athlete health, well-being and integrity caused by non-accidental violence through harassment and abuse. All athletes have a right to engage in `safe sport`, defined as an athletic environment that is respectful, equitable and free from all forms of non-accidental violence to athletes. Yet, these issues represent a blind spot for many sport organisations through fear of reputational damage, ignorance, silence or collusion. This consensus statement extends the 2007 IOC Consensus Statement on Sexual Harassment and Abuse in Sport, presenting additional evidence of several other types of harassment and abuse—psychological, physical and neglect. All ages and types of athletes are susceptible to these problems but science confirms that elite, disabled, child and lesbian/gay/bisexual/trans-sexual (LGBT) athletes are at highest risk, that psychological abuse is at the core of all other forms and that athletes can also be perpetrators. Harassment and abuse arise from prejudices expressed through power differences. Perpetrators use a range of interpersonal mechanisms including contact, non-contact/verbal, cyber-based, negligence, bullying and hazing. Attention is paid to the particular risks facing child athletes, athletes with a disability and LGBT athletes. Impacts on the individual athlete and the organisation are discussed. Sport stakeholders are encouraged to consider the wider social parameters of these issues, including cultures of secrecy and deference that too often facilitate abuse, rather than focusing simply on psychopathological causes. The promotion of safe sport is an urgent task and part of the broader international imperative for good governance in sport. A systematic multiagency approach to prevention is most effective, involving athletes, entourage members, sport managers, medical and therapeutic practitioners, educators and criminal justice agencies. Structural and cultural remedies, as well as practical recommendations, are suggested for sport organisations, athletes, sports medicine and allied disciplines, sport scientists and researchers. The successful prevention and eradication of abuse and harassment against athletes rests on the effectiveness of leadership by the major international and national sport organisations.